(untitled) (Acta Scientiarum. Health Sciences, 2024)
Telepsychiatry, which refers to the delivery of mentalhealth services throughvideo-based conferencing, has immense potential to resolve the mental health disparities. Era of telepsychiatry came into full force during the COVID -19 pandemic in the year 2020 in India. The literature on profile of patients attending a telepsychiatry unit is limited as the official guidelines for Telemedicine was released by the government of India in March 2020. This article provides a state-of-art analysis on the profile, telehealth usability, diagnosis, drug treatments of patients attending a telepsychiatry unit in a Union Territory in south India. 1. To profile the telepsychiatry usability by using standard questionnaire. 2. To compare the telepsychiatry usage between 2020 and 2021 (during lockdown 1 & lockdown 2). A retrospective analysis of the profile of patients attending a telepsychiatry unit in south India during the consecutive years of 2020 and 2021 was made. Demographic data regarding the age, sex, marital status, occupation, location, number of online consultations made were collected. Diagnosis was made in accordance with the International Classification of diseases tenth edition. Various groups of drugs used like antidepressants, antipsychotics, mood stabilisers, benzodiazepines. Comparison of data between the two years was made. In the year 2020, 147 teleconsultations were made and in the year 2021 46 consultations were done. Among the study participants, 62% were female. In the year 2020, psychosis was found to be the reported more(34%) and in 2021, adjustment disorder was higher (35%). Among the medications, antidepressants (35%) were the commonly prescribed group followed by antipsychotics(13%). Telepsychiatry is a budding phenomenon in India and this study is the first of its kind to throw light on the profile, drug treatment of patients attending a telepsychiatry set up.